THE INFLUENCE OF BRAND IMAGE, LIFESTYLE, PROMOTION AND PRICE ON OPPO MOBILE PHONE PURCHASE DECISIONS AT ANUGERAH KARYA ABADI KEDIRI STORE - Lusianto, Kefri Septian (Universitas Airlangga, 2024)
This research uses quantitative methods and the population studied is all consumers who purchased Oppo cellphones within the 3 month research period. The number of samples taken was 97 respondents, the sampling method used purposive sampling. Data were collected through questionnaires, while analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, R2 determinant test, t-test, and f test. The research results show that (1) brand image partially influence on purchasing decisions with a t value of -2.050 and a sig value. 0.043 < 0.05, (2) lifestyle partially influence on purchasing decisions with a t value of 5.076 and a sig value. 0.000 < 0.05, (3) promotion partially influence on purchasing decisions with a t value of 3.403 and a sig value. 0.001 < 0.05, (4) price partially influence on purchasing decisions with a t value of 2.212 > t table and a sig value. 0.029 < 0.05, (5) brand image, lifestyle, promotion, and price simultaneously influence on purchasing decisions with an F-count value of 17.708 and a sig value. F 0.000 < 0.05. Through the results of the calculations that have been carried out, there was an influence between promotions on purchasing decisions as well as price on purchasing decisions. The influence of brand image is quite important in strengthening the store's image so that it is effective in increasing purchasing decisions. This can be done through more intensive branding efforts, including consistent use of logos, clear brand messages, and a satisfying customer experience.